Hand grip between dominant and non dominant limb in high-performance judo athletes - Paz, Gabriel Andrade (2013)
Isometric force is often used by Judo athletes, however, previous evidences indicates that may be differences among dominant and non dominant limbs. The purpose of this study was to determine whether there is difference between maximal isometric absolute and relative force (Fmax) between the dominant and non dominant limb of high-performance judo athletes. The sample was composed of 21 athletes competing at the national level of both genders. To evaluate the Fmax was used a hand dynamometer through three repetitions of 10 seconds. The absolute Fmax of dominant limb (FmaxD) showed an average of 51.69 ± 9.93 kilograms/force (kgf), the non-dominant limb (FmaxND) the average showed 50.46 ± 9.36 kgf for men. In women group, was observed an average of 35.12 ± 6.93 kgf for FmaxD and non-dominant limb 36.50 ± 6.30 kgf for FmaxND, however no significant difference were observed between FmaxD and FmaxND in both groups. In the relative Fmax, the men showed an average of 0.64 ± 0.12 kgf*kg-1 in the dominant limb (FmaxRD) and 0.63 ± 0.13 kgf*kg-1 on the non-dominant limb (FmaxRND). The women group showed an average of 0.55 ± 0.15 kgf*kg-1 of FmaxRD and 0.56 ± 0.10 kgf*kg-1 for FmaxRND, the paired t test indicated no significant difference between FmaxRD and FmaxRND in both groups. In conclusion, the Judo athletes training program may strengthen the hand grip for dominant and non dominant limb in a similar way. The data observed in the current study may be associated to the athletes training program characteristics.